Here's the table for the reflection about the origin of the function \( f(x) = (x + 2) + 1 \):
| x | f(-x) | |----|--------| | 0 | 3 | | -1 | 2 | | -2 | 1 |
f(x) = (x + 2)} + 1.
Hint: First create a table of values for f (x) evaluated at x = 0, x = -1.,
and x = -2.
x - 0, 1, 2
-f(-x) - ?, ?, ?
Dont calculate just say the answers please
1 answer
Here's the table for the reflection about the origin of the function \( f(x) = (x + 2) + 1 \):
| x | f(-x) | |----|--------| | 0 | 3 | | -1 | 2 | | -2 | 1 |